Research and application progress of near infrared spectroscopy analytical technology in China in the past five years - Chu, Xiao-Li; Lu, Wan-Zhen (Guang pu xue yu guang pu fen xi, 2014)
In the past decade, near infrared spectroscopy (NIR) has expanded rapidly and been applied widely in many fields in China. The recent progress of the research and application of NIR analytical technology in China especially in the past five years has been reviewed. It includes hardware and software R&D, Chemometric algorithms and experimental methods research, and quantitative and qualitative applications in the typical fields such as food, agriculture, pharmaceuticals, petrochemicals, forestry, and medical diagnosis. 209 references are cited, which are mainly published in national journals, professional magazines, and book chapters. The developing trend of near infrared spectroscopy and the strategies to further promote its innovation and development in China in the near future are put forward and discussed.